Bener Meriah لترقية قدرة الطلاب على سيطرة المفردات بمعهد نور الإسلام (Explosion Box ) استخدام وسيلة الصندوق الانفجاري - Mahmud, Salami; Fajriah, Fajriah; Hikmah, Hkmah (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2024)
Based on the first observation, the researchers found problems at the Nurul Islam Integrated Islamic Boarding School students had not mastered mufradat when speaking and the teacher's habit in the teaching and learning process was to only use a blackboard, so students felt tired and sleepy. Based on the problems above, researchers are interested in using Explosion Box media to improve students' abilities in mastering mufradat. The aim of this research is to determine the effectiveness of students' mastery of mufradat using Explosion Box media at the Nurul Islam Bener Meriah Integrated Islamic Boarding School. Researchers used an experimental method with a one group pre-test and post-test design type, researchers use tests in collecting data. The population in this study were all first grade students at the Nurul Islam Integrated Islamic Boarding School for the 2023/2024 academic year for the tsanawiyah level, and class 1a2 as the sample in this study, totaling 24 students. The conclusion obtained is that the use of Explosion Box media is effective in improving students' abilities in mastering mufradat. This is proven based on the sig value of the T test showing 0.00 which is smaller than 0.05. Based on these values, the null hypothesis (Ho) is rejected and hypothesis a (Ha) is accepted.